Kinetics of Anaerobic Co-Digestion of Paunch Manure and Sugarcane Peels using Cow Dung as Inoculum - Abdulhakeem, N. H.; Lawal, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Anaerobic co-digestion offers a prospective medium for transforming organic solid wastes into fuel, thereby providing an extra source of energy. This study investigates the kinetics of anaerobic co-digestion of paunch manure and sugarcane peels using cow dung as inoculum for biogas production. Anaerobic assay setup was in 3 digesters of 4 replicates with a total of 12 replicate batch digesters under mesophilic temperature range (30-35°C) for a retention time of 30 days. Cumulative biogas production for all digesters were measured and fitted to some selected models. The modified Gompertz equation was tested for its fitness. The kinetic parameters viz., biogas yield potential (P), maximum biogas production rate (Rm) and the duration of lag phase (λ) were recorded for each case as the digester with 0g sugarcane peels (control) produced maximum biogas of (83.14 (mL/g VS)) and the kinetic parameters P, Rm and λ were 89.0018 ml (g VS-1), 4.7089 ml (g VS d)-1, 0.8734 days respectively. It was observed that biogas production potential was inversely proportional to the substrate concentration of sugarcane peels in the digesters, the highest concentration of sugarcane peels (1.8g SP) recorded the lowest quantity of biogas with 37.9075 mL/g VS, 1.4547 g VS-1, 1.0891 days. Therefore, sugarcane peels should be co-digested with other substrates. The experimental kinetic data in-line with the Gompertz Model, Modified Gompertz Model Equation.